MAKANAN HANTARAN PADA UPACARA PERKAWINAN DI DESA SUNGAI ABU KECAMATAN HILIRAN GUMANTI KABUPATEN SOLOK PROVINSI SUMATERA BARAT - Sofnitati Sofnitati (Fakultas Pariwisata dan Perhotelan Universitas Negeri Padang, 2018)
This study aims to reveal: 1)a series of Hantaran custom ceremony, 2) type of Hantaran custom food, 3) equipment used to bring Hantaran custom food, 4) the meaning of food at Hantaran Ceremony. The type of this research is qualitative research, the object of research is Hantaran custom food that is brought on The Hantaran event in the Sungai Abu Vilage. The result showed that the Hantaran event in The Sungai abu Village held the second day at the wedding ceremony., the series of Hantaran events in Sungai Abu Vilage has two stages of preparation before the event and the series of Hantaran custom ceremonies, the type of food served at the Hantaranceremony as many as 23 types and their meaning as a symbol of